PENGARUH PENERAPAN PEMBELAJARAN DARING DAN PEMBELAJARAN MODEL ARCS TERHADAP PENINGKATAN KARAKTER RELIGI SISWA KELAS 6 SDN KEMAYORAN 1 BANGKALAN - NURHAYATI EKA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
The purpose of this study was to determine the effect of online learning and learning ARCS (Attention, Relevance, Confidence, and Satisfaction) models on increasing the religious character of 6th grade students at SD Negeri Kemayoran 1 Bangkalan, implementing online learning (variable X1) and learning ARCS models as variables. independent (variable X2), as well as the student religious attitude variable as the dependent variable (variable Y), with measurement using a Likert scale 1-5. The population in this study were all grade 6 students at SD Negeri Kemayoran 1 Bangkalan, totaling 31 people, using multiple regression data analysis. The results showed that the resulting regression modeling was Y = -0.078 + 0.187 X1 + 0.828 X2, which means that the existence of online learning and ARCS Model Learning partially and simultaneously affects the religious attitudes of 6th grade students of SD Negeri Kemayoran 1 Bangkalan, the two variables The dominant effect on the religious attitudes of grade 6 students is the ARCS Learning Model.